Adverse Childhood Experiences, sexual debut and substance use among Black justice-involved youth: The imperative of trauma-informed sexuality education. (April 2023) - Williams-Butler, Abigail; Howard, Tyriesa; Li Anthony, Wen; Duron, Jacquelynn
Highlights: Among Black justice-involved youth ACEs predict substance use initiation, cannabis initiation and early sexual debut. More ACEs are significantly related to higher odds of having earlier sexual debut, alcohol use initiation, and cannabis use initiation after controlling for age and gender. ACEs had a significantly indirect effect on having sex under the influence through.sexual debut and cannabis use initiation. Sexual health decision-making of justice-involved adolescents can be better supported. Through trauma-informed sexuality education. Trauma-informed sexuality education offers enhanced skills for sexual health decision making to reduce negative sexual health outcomes. Abstract: The purpose of this study is to determine how Adverse Childhood Experiences (ACEs) influence the age of sexual debut and the age of substance use initiation among a sample of Black justice-involved youth. A total of 368 Black adolescents (52.7 % female, 11–17 years of age) arrested and detained in Cook County, IL completed assessments as part of the Northwestern Juvenile Project. At baseline, adolescents self-reported sexual debut, substance use initiation (cannabis/marijuana and alcohol), and history of ACEs. Data were analyzed using multivariate path analyses to examine the effects of ACEs on sexual debut, substance use initiation, and engagement in sex under the influence. Age and gender were used as covariates. Results indicate that most participants (97 %) experienced at least one adverse childhood experience and the majority (82 %) reported a very early (11–12 years) or early sexual debut (13–14 years). More ACEs were significantly related to higher odds of having earlier sexual debut ( OR  = 1.23, p  < 0.001), alcohol use initiation ( OR  = 1.31, p  < 0.01), and cannabis use initiation ( OR  = 1.23, p  < 0.01) after controlling for age and gender. ACEs had a significantly indirect effect on having sex under the influence only through sexual debut ( β  = 0.08, 95 % CI: 0.03, 0.17) and cannabis use initiation ( β  = 0.11, 95 % CI: 0.02, 0.25). Findings imply that the sexual health decision-making of justice-involved adolescents can better be supported through trauma-informed sexuality education that gives primacy to acknowledging their experiences with trauma as a critical part of their rehabilitative treatment. This study on ACEs among Black justice-involved youth documents prevalent adversity that predicts early sexual debut, substance use initiation, and sex under the influence. Findings imply trauma-informed sexuality education as a viable option for justice-involved youth to learn enhanced skills for informed sexual health decision-making to reduce negative sexual health outcomes.